Simple and Novel Approach for Image Representation with Application to Face Recognition - Eleyan, Alaa (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In this paper a new statistical image descriptor for the face recognition problem is proposed. To the best of our knowledge, no one has attempted to implement this approach before. The idea is simple and straight forward. For each face image, a feature descriptor is formed by concatenating 4 vectors together. These four vectors are formed by taking the sum of pixels in four different directions, namely; row-wise sum (0), column-wise sum (90 ), diagonal-wise sum (45 ) and antidiagonal-wise sum (-45 ). For test purposes, the generated feature descriptor is used in face recognition problem. The experiments are carried out on two different face databases namely; ORL and PUT databases. Simulation results show that the proposed approach gave a comparative performance to the well-known feature extraction algorithms in face recognition.